Impact of the Acceptance of the Recommendations Made by a Meropenem Stewardship Program in a University Hospital: A Pilot Study - Jorge Alba Fernandez; Jose Luis del Pozo; Jose Leiva; Mirian Fernandez-Alonso; Irene Aquerreta; Azucena Aldaz; Andres Blanco; Jose Ramón Yuste (MDPI AG, 2022)
Antimicrobial stewardship programs (ASP) promote appropriate antimicrobial use. We present a 4-year retrospective study that evaluated the clinical impact of the acceptance of the recommendations made by a meropenem-focused ASP. A total of 318 meropenem audits were performed. The ASP team (comprising infectious disease physicians, pharmacists and microbiologists) considered meropenem use in 96 audits (30.2%) to be inappropriate. The reasons to consider these uses inappropriate were the possibility of de-escalating to a narrower-spectrum antibiotic, in 66 (68.7%) audits, and unnecessary meropenem use, in 30 (31.3%) audits. The ASP team recommended de-escalation in 66 audits (68.7%) and discontinuation of meropenem in 30 audits (31.3%). ASP interventions were stratified according to whether or not recommendations were followed. The group in which recommendations were accepted and followed (i.e., accepted audit, AA) included 66 audits (68.7%) and the group in which recommendations were not followed (i.e., rejected audit, RA) included 30 (31.3%) audits. The comorbidity of the AA group (Charlson score) was higher than in the RA group (7.0 (5.0-9.0) vs. 6.0 (4.0-7.0), p = 0.02). Discontinuation of meropenem was recommended in 83.3% of audits in the AA group vs. 62.2% in the RA group (OR 3.05 (1.03-8.99), p = 0.04). Ertapenem de-escalation resulted in a 100% greater rate of follow-up compared with the non-carbapenem option (100% vs. 51.9%, OR 1.50 (1.21-1.860), p = 0.001). Significant differences were observed in the AA group when cultures were taken before antibiotic prescription-98.5% vs. 83.3% (p = 0.01, OR 13.0 (1.45-116.86))-or when screening cultures were taken-45.5% vs. 19.2% (p = 0.03, OR 3.5 (1.06-11.52)). There were no differences between the groups in terms of overall mortality and 30-day mortality, length of stay, Clostridiodes difficile infection, 30-day readmission or hospitalization costs. In conclusion, meropenem ASP recommendations contributed to a decrease in meropenem prescription without worsening clinical and economic outcomes.